2006
DOI: 10.1007/s10661-006-9443-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bulk Deposition in Protected Woodland Area in Western Poland

Abstract: Research on precipitation carried out systematically at the University station at Jeziory in the Wielkopolski National Park (western Poland) allowed the determination of pollutants deposited with precipitation in this forest ecosystem. During 13 years of study, the pH of precipitation was found to persist at a low level (4.33 on average), which resulted a substantial deposition of H(+). Values of acidifying and basic ions deposited in this area were determined and compared with the respective figures obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…This was also confirmed by our results. H + depositions, which represented acidity of rainfall, are higher in the mountains and increases with the amount of rainfall (Walna & Kurzyca 2007). Our results also support this finding.…”
Section: The Ph Development In Depositionssupporting
confidence: 88%
See 1 more Smart Citation
“…This was also confirmed by our results. H + depositions, which represented acidity of rainfall, are higher in the mountains and increases with the amount of rainfall (Walna & Kurzyca 2007). Our results also support this finding.…”
Section: The Ph Development In Depositionssupporting
confidence: 88%
“…According to Walna & Kurzyca (2007), rigid structure representation cations may indicate a stabilization of emission sources. Thöni (2008) did not find a reduction in the deposition of the elements Na, Mg, Ca and K but in Slovakia, the statistically significant changes were determined.…”
Section: The Development Of Basic Cations and Sulfur And Nitrogen Commentioning
confidence: 99%
“…Consequently, several research programmes have been initialed to study atmospheric N deposition in forests, such as the large-scale European NITREX (Nitrogen saturation experiment), SFONE (Swedish Forest Optimum Nutrition Experiments), and EANET (Acid deposition monitoring network in East Asia). These programmes found that "N saturation" appeared in many forests, i.e., in Poland and many parts of Europe (Fischer et al, 2007;Walna and Kurzyca, 2007). However, researches on N deposition in China have primarily focused on heavily polluted regions, and only few measurements have been conducted in forests (Fang et al, 2011;Zhao et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In order to do so, the use of the results of the research conducted by international network, e.g. the European Background Monitoring Network (EMEP), is recommended [60,61].…”
Section: International Journal Of Environmental Analytical Chemistry 913mentioning
confidence: 99%